Dynamic of changing functional and physical 19–35 year-old women’s state on the basic of self-training with using of health-improving kinds of physical culture - Шамардіна (Shamardina G.) Галина Миколаївна; Мартынюк (Martynyuk O.) Ольга Вікторівна (Slobozhanskyi Herald of Science and Sport, 2012)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> The article represents the comparative analysis results of physical data of 19–35 year-old women before and after 4 months self-training with using of different health-improving kinds of physical culture (athletic gymnastic, swimming, shaping). <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>